Ablation at Right Coronary Cusp as an Alternative and Favorable Approach to Eliminate Premature Ventricular Complexes Originating From the Proximal Left Anterior Fascicle. (May 2020) - Chen, Songwen; Lu, Xiaofeng; Peng, Shi; Xue, Yumei; Zhou, Genqing; Ling, Zhiyu; Wei, Yong; Yang, Keping; Fu, Wenjun; Cai, Lidong; Xu, Juan; Ouyang, Feifan; et al.
Abstract : Background: Premature ventricular complex (PVC) with narrow QRS duration originating from proximal left anterior fascicle (LAF) is challenging for ablation. This study was performed to evaluate the safety and feasibility of ablation from right coronary cusp (RCC) for proximal LAF-PVC and to investigate this PVC's characteristics. Methods: Mapping at RCC and left ventricle and ECG analysis were performed in 20 patients with LAF-PVC. Results: The earliest activation site (EAS), with Purkinje potential during both PVC and sinus rhythm, was localized at proximal LAF in 8 patients (proximal group) and at nonproximal LAF in 12 patients (nonproximal group). The Purkinje potential preceding PVC-QRS at the EAS in proximal group (32.6±2.5 ms) was significantly earlier than that in nonproximal group (28.3±4.5 ms, P =0.025). Similar difference in the Purkinje potentials preceding sinus rhythm QRS at the EAS was also observed between proximal and nonproximal groups (35.1±4.7 versus 25.2±5.0 ms, P <0.001). In proximal group, the distance between the EAS to left His bundle and to RCC was shorter than that of nonproximal group (12.3±2.8 versus 19.7±5.0 mm, P =0.002, and 3.9±0.8 versus 15.7±7.8 mm, P <0.001, respectively). No difference in the distance from RCC to proximal LAF was identified between the 2 groups. PVCs were successfully eliminated from RCC for all proximal groups but at left ventricular EAS for nonproximal groups. The radiofrequency application times, ablation time, and procedure time of nonproximal group were longer than that of proximal group. Electrocardiographic analysis showed that, when compared with nonproximal group, the PVCs of proximal group had narrower QRS duration; smaller S wave in leads I, V5, and V6 ; lower R wave in leads I, aVR, aVL, V1, V2, and V4 ; and smaller q wave in leads III and aVF. The QRS duration difference (PVC-QRS and sinus rhythm QRS) <15 ms predicted the proximal LAF origin with high sensitivity and specificity. Conclusions: PVCs originating from proximal LAF, with unique electrocardiographic characteristics, could be eliminated safely from RCC. Abstract : Supplemental Digital Content is available in the text.